PENGARUH CORPORATE GOVERNANCE, RETURN ON ASSET DAN UMUR PERUSAHAAN TERHADAP LUAS PENGUNGKAPAN SUSTAINABILITY REPORT (Studi Kasus pada Perusahaan LQ-45 periode 2017-2019) - Kamisa Delasari; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2022)
In the era of globalization, sustainability reporting can be a differentiator in industry competition. Business stakeholders need better information about how environmental, social and economic impacts factor into business strategies and decisions. The purpose of this study was to determine the effect of corporate governance as measured by the ASEAN Corporate Governance Scorecard (ACGS) level 1 indicators, Return on Assets (ROA) and company age on the extensive disclosure of sustainability reports. The level of disclosure of sustainability reports is measured by instruments in the GRI Global Reporting Initiative (GRI) Standards. The sample used in this study are companies that are consistently listed on the 2017-2019 LQ45 Index. Sampling was carried out by purposive sampling and resulted in 11 (eleven) companies being selected as the final sample. The statistical method used is the multiple linear regression method, with the t statistical hypothesis test using a significance level (α) = 5%. The statistical tool used is SPSS 16. The results show that return on assets has a significant positive effect on the extent of disclosure of the sustainability report, while corporate governance and company age have no significant effect on the extent of disclosure of the sustainability report.Keywords : Corporate Governance, Return On Asset, Company Age, and Sustainability Report